1987
DOI: 10.3171/jns.1987.66.4.0542
|View full text |Cite
|
Sign up to set email alerts
|

The impact-absorbing effects of facial fractures in closed-head injuries

Abstract: A series of 210 patients with facial fractures sufficiently severe to require cranial computerized tomography (CT) to evaluate suspected closed-head injury (CHI) was studied. The injuries were separated into five grades of severity based on neurological examination, including cranial CT. The injuries were also grouped into three categories based on facial regional involvement, using chi-square contingency table analysis. The data demonstrated that patients with upper facial fractures were at greatest risk for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
58
6
8

Year Published

1988
1988
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(80 citation statements)
references
References 22 publications
8
58
6
8
Order By: Relevance
“…Embora se saiba que TCE leve não seja irrelevante, escolhemos focalizar os grupos de TCE moderado-grave para avaliar melhor o espectro da relação de trauma de face e acometimento simultâneo de encéfalo. Acometimento primário do encéfalo foi muito incomum em nosso trabalho, suportando o clássico trabalho de Sturla et al 17 da existência de "pilares" de sustentação craniofacial que determinam linhas de fratura anatomicamente relacionadas ao local e intensidade do impacto; nossos dados são ainda favorecidos pela teoria de que os ossos da face absorvem impacto pois são preenchidos por ar, servindo de coxim de proteção para o cérebro 18 . Porém, ainda não existe consenso, de modo que Martin et al 19 e Davidoff et al 16 consideram que as fraturas de face são marcadores para TCE grave e não protetores do encéfalo.…”
Section: Discussionunclassified
“…Embora se saiba que TCE leve não seja irrelevante, escolhemos focalizar os grupos de TCE moderado-grave para avaliar melhor o espectro da relação de trauma de face e acometimento simultâneo de encéfalo. Acometimento primário do encéfalo foi muito incomum em nosso trabalho, suportando o clássico trabalho de Sturla et al 17 da existência de "pilares" de sustentação craniofacial que determinam linhas de fratura anatomicamente relacionadas ao local e intensidade do impacto; nossos dados são ainda favorecidos pela teoria de que os ossos da face absorvem impacto pois são preenchidos por ar, servindo de coxim de proteção para o cérebro 18 . Porém, ainda não existe consenso, de modo que Martin et al 19 e Davidoff et al 16 consideram que as fraturas de face são marcadores para TCE grave e não protetores do encéfalo.…”
Section: Discussionunclassified
“…Whereas most of the authors like Bank, Lee et al [15,4] reported that facial fractures are associated with a decreased risk of brain injury, Davidoff et al [20] and very recently Keenan and others [21] found facial fracture to be highly associated with traumatic brain injury. They concluded that facial bones might not act as cushion to protect the brain against impact but infact are markers for increased risk of brain injury.…”
mentioning
confidence: 99%
“…Lee et al [4] in the discussion of biomechanical aspects of facial trauma state that: In motor-vehicle collisions, the head is often subjected to forces many times that of gravity. As fractures occur, the facial skeleton absorbs some of the impact and cushions the brain against some of its violent effects.…”
mentioning
confidence: 99%
See 2 more Smart Citations